Electrochemical synthesis of luminescent MoS2 quantum dots. Issue 29 (9th February 2015) - Gopalakrishnan, Deepesh; Damien, Dijo; Li, Bo; Gullappalli, Hemtej; Pillai, Vijayamohanan K.; Ajayan, Pulickel M.; Shaijumon, Manikoth M.
Abstract : Quantum dots of single-/few-layered MoS2 with tunable sizes, obtained through a unique electrochemical exfoliation process, show excellent electrocatalytic activity towards hydrogen evolution reactions. Abstract : Size-controlled synthesis of luminescent quantum dots of MoS2 (≤2 layers) with narrow size distribution, ranging from 2.5 to 6 nm, from their bulk material using a unique electrochemical etching of bulk MoS2 is demonstrated. Excitation-dependent photoluminescence emission is observed in the MoS2 QDs. "As-synthesized" MoS2 QDs also exhibit excellent electrocatalytic activity towards hydrogen evolution reactions.